2017
DOI: 10.1039/c7mb00390k
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative investigation of MDA-MB-231 breast cancer cell motility: dependence on epidermal growth factor concentration and its gradient

Abstract: Enhanced cell motility is one of the primary features of cancer. Accumulated evidence demonstrates that Epidermal Growth Factor Receptor (EGFR) mediated pathways play an important role in breast cancer cell proliferation and migration. We have quantified the MDA-MB-231 breast cancer cell migration in response to the stimulation of EGFR pathways with its ligand EGF to determine how cell motility of MDA-MB-231 cells depend on the ligand concentration and its gradient. Analysis at the single cell level combined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 60 publications
4
18
0
Order By: Relevance
“…Cell proliferation assay was first performed on MCF7 and MDA-MB-231 cells, confirming the higher proliferation of the latter, in agreement with the literature (Figure 2a) (Gest et al, 2013; H. et al, 2011; Islam & Resat, 2017). The activity and functionality of the isolated 231_sEVs were evaluated by verifying differences in MCF7 cell proliferation upon the addition of 231_sEVs.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Cell proliferation assay was first performed on MCF7 and MDA-MB-231 cells, confirming the higher proliferation of the latter, in agreement with the literature (Figure 2a) (Gest et al, 2013; H. et al, 2011; Islam & Resat, 2017). The activity and functionality of the isolated 231_sEVs were evaluated by verifying differences in MCF7 cell proliferation upon the addition of 231_sEVs.…”
Section: Resultssupporting
confidence: 89%
“…To test such assumption, we examined the effects of small EVs derived from the TNBC MDA-MB-231 breast cancer cells on the stiffness, cytoskeleton organization, nuclear/cellular morphology, and Yap activity of the Luminal A MCF7 breast cancer cells. The two cell lines have been chosen according to their different well-defined metastatic potential: MDA-MB-231 cells are characterized by high proliferation, motility, and metastatic rate (Islam & Resat, 2017), whereas MCF7 cells are tumorigenic but have low/absent metastatic potential (Gest et al, 2013;H. et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…4A). The induction of EGF on cell migration and invasion was confirmed by previous studies [27,28]. We also evaluated the role of EGF in our research system.…”
Section: Hnrnpa2/b1 Knockout Promotes F-actin Cytoskeleton Formation and Emt In Human Breast Cancer Cellssupporting
confidence: 71%
“…The results of the present study suggested that TSLNC8 was downregulated in human glioma, which was associated with increased cell proliferative rate and cell metastasis, as well as the decreased cell apoptotic capacity in human glioma cell lines; TSLNC8 may be a potential therapeutic target for cancer patients in clinic. Cell proliferation and cell metastasis are two primary manifestations in the majority of malignancies (24,25). Initiation of metastasis requires invasion, which was examined in the present study via Transwell and wound-healing assays.…”
Section: Discussionmentioning
confidence: 99%